House Construction Contracting Agreement Viewed From Civil Law Perspective - Muhammad Nurohim (Sean Institute, 2025)
The house construction contracting agreement is one of the named forms of agreement specifically regulated in the Civil Code. The purpose of this research is to find out about the arrangement of the house construction contracting agreement in terms of civil law. This type of research is normative with a conceptual and statutory approach. The nature of the research is descriptive analytical. The data used is secondary data consisting of primary and secondary legal materials while data analysis is carried out qualitatively. The contracting agreement is regulated in Chapter 7 A of Book III, Article 1601 b to Article 1616 of the Civil Code. Article 1601 b of the Civil Code states that a work contracting agreement is an agreement that the first party, namely the contractor, binds himself to complete a job for the other party, namely the employer. In a contracting agreement, there is one party who buys work (bouwheer) with another party who is obliged to buy work (contractor / contractor), where the first party wants a work result that is agreed upon by the opposing party, upon payment of an amount of money as a contracting price. For this reason, it is recommended that the agreement be carried out in good faith by the parties to avoid disputes.